Pengaruh Self-Qongruity Terhadap Word of Mouth Intention Jasa Pendidikan yang Dipilih - Pamula, Mahardhika (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
In an era of increasingly fierce competition between higher education institutions, the image of the institution and the perception of students play an important role in shaping loyalty as well as non-formal promotional actions such as word of mouth (WOM). One of the psychological factors that affect this behavior is self-congruity, which is the extent to which the institution's image matches the student's self-image. When students feel that there is a compatibility between their personal values and the characteristics of the institution, there will be an emotional attachment that encourages them to recommend the institution to others, either directly or through social media. This study aims to analyze the influence of self-congruity on word of mouth intention in students of the Elementary School Teacher Education Study Program (PGSD) STKIP Modern Ngawi. Self-congruity refers to the degree of compatibility between the student's self-image and the institution's image, while word of mouth intention reflects the student's intention to recommend the institution to others. The research method used is quantitative with the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The research sample amounted to 100 students in semesters 6 and 8 who were selected through purposive sampling techniques. The results of the analysis showed that self-congruity had a positive and significant effect on word of mouth intention, with a path coefficient value of 0.239 and a p value of 0.024. The R-square value of 0.057 indicates that the influence of self-congruity on word of mouth intention is significant but is still influenced by other factors outside the study variables. These findings show that the compatibility between students' self-perception and campus image contributes to shaping the intention to disseminate positive information about higher education institutions. Therefore, the institution is advised to build a campus image that reflects students' personal values to strengthen their loyalty and involvement.